The Development of Arithmetic Gamification Using Digital Dice - Widodo, Suprih; Rahayu, Puji; Adjie, Nahrowi; Adi Widodo, Sri; Rahmat Setiadi, Bayu (International Journal of Engineering and Technology, 2018)
Due to the importance of arithmetic abilities for elementary school students, this research aims to develop games using digital dice.This games will be used in gamification in math education. This research method is research and development, while the game development process using the waterfall model of system development life cycle. Based on the results of development, the system is built so that the students are emotionally engaged through digital dice games, they didnâ€™t only tap the screen or answer the exercise. The results of functional testing and compatibility also show that the system has excellent functionality and compatibility. Â